Correction: Development of a reverse transcription recombinase polymerase amplification assay for rapid and direct visual detection of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). - Yee Ling Lau; Ilyiana Binti Ismail; Nur Izati Binti Mustapa; Meng Yee Lai; Tuan Suhaila Tuan Soh; Afifah Haji Hassan; Kalaiarasu M Peariasamy; Yee Leng Lee; Maria Kahar Bador Abdul Kahar; Jennifer Chong; Pik Pin Goh (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0245164.].